"Tak Lagi Sama": Pergeseran Makna Pernikahan pada Ibu Muda yang Bercerai - Siti Jaro'ah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The number of divorce cases in Indonesia continues to increase, and this experience can affect one’s perception of marriage. This study aims to explore in more depth the meaning of marriage that young, divorced mothers have. This research is phenomenological qualitative research. The data were collected by means of semi-structured interviews and analyzed using descriptive analysis. The results revealed 5 (five) aspects, namely: 1) the meaning of marriage before marriage, 2) the meaning of marriage after divorce, 3) reasons for divorce, 4) decision to remarry, and 5) children for participants. The research revealed that marriage, which was originally a life goal, changed due to bad experiences during marriage and divorce.